Clinical Characteristics of Visual Dysfunction in Carbon Monoxide Poisoning Patients - Wei-Kang Bi; Jin-Lin Wang; Xu-Dong Zhou; Ze-Kun Li; Wen-Wen Jiang; Shao-Bin Zhang; Yong Zou; Ming-Jun Bi; Qin Li (Journal of Ophthalmology)
Purpose. The aim of the present study was to analyze the clinical characteristics of visual dysfunction in patients with carbon monoxide (CO) poisoning. Methods. A total of 436 patients with CO poisoning were enrolled in our hospital from October 2012 to December 2018, including 193 patients with moderate poisoning (MP group), 165 with severe poisoning (SP group), and 78 with delayed encephalopathy (DE group). The clinical characteristics of visual dysfunction in patients with CO poisoning were analyzed through the collection of medical history, regular physical examination, brain magnetic resonance imaging (MRI), ophthalmological examination, the National Eye Institute Visual Function Questionnaire (NEI-VFQ), and its influencing factors. Results. Some patients in the three groups had visual dysfunction. The main ocular symptoms were local pain, eye movement disorder, and visual field defect. The key pathological factors were keratopathy, retinal nerve cell damage, optic nerve damage, retinal vascular disease, macular disease, and occipital visual center damage. The clinical symptoms of visual dysfunction after CO poisoning lasted for a long time (>12 months) and were not completely consistent with the positive results of the ophthalmological examination. A few sequelae of ophthalmology were still left after the help of medicine. Conclusion. The incidence of visual dysfunction in patients with CO poisoning was high, the clinical symptoms were rich and diverse, the duration of disease was long, and the prognosis was poor. Thus, the relevant ophthalmological examination and intervention treatment should be perfected as soon as possible.